Bactericidal Effect of Hydrogen Peroxide on Spacecraft Isolates - Wardle, M. D. (1975)
Solutions of 3, 10, and 15% hydrogen peroxide were found to have pronounced bactericidal effects, as a function of time of exposure, on sporeformers and non-sporeformers isolated from spacecraft.